HUBUNGAN FAKTOR DEMOGRAFI DENGAN PENGETAHUAN CARA PENGGUNAAN OBAT BEBAS & BEBAS TERBATAS DI KELURAHAN PENGGILINGAN - Dessy Adelia Pramesty; Charles; Niko Prasetya (Jurnal Farmasi IKIFA, 2024)
Drugs play a very important role in health services. Treatment and prevention of various diseases cannot be separated from therapeutic actions with drugs or pharmacotherapy. Based on the results of the 2013 Basic Health Research, it showed that as many as 103,860 households or 35.2% of the 249,959 households in Indonesia kept medicines for self-medication, with the highest proportion of households in DKI Jakarta 56.4%. The purpose of this study was to determine the description of free and limited over-the-counter drug storage in the form of tablets, capsules and liquid or syrup preparations in the community. This study used a descriptive method by means of simple random sampling. There are 144 sample in this study were people who had family cards and ID cards registered in Penggilingan Village. The results showed that of the 144 respondents who had good knowledge 70 people (48.61%) had sufficient knowledge 67 people (46.53%) hand insufficient 7 people (4.86%). Based Based on statistical calculations with the Spearman rho test, it shows that there is no relationship between age and the level of knowledge regarding supplement storage because the sig value (0.053) > 0.05. Keywords : Knowledge, supplement storage, Spearman rho